A constrained approximation problem arising in parameter identification - Jacob, Birgit; Leblond, Juliette; Marmorat, Jean-Paul; Partington, Jonathan R. (Linear algebra and its applications, 2002)
We pose and solve an extremal problem in the Hardy class H 2 of the disc, involving the best approximation of a function on a subarc of the circle by a H 2 function, subject to a constraint on its imaginary part on the complementary arc. A constructive algorithm is presented for the computation of such a best approximant, and the method is illustrated by a numerical example. The whole problem is motivated by boundary parameter identification problems arising in non-destructive control.